2006
DOI: 10.1038/sj.bjp.0706663
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of adenosine‐induced airways obstruction in allergic guinea pigs

Abstract: 1 Inhaled adenosine induces airway obstruction in asthmatic but not healthy subjects, a phenomenon that is also observed in various animal species when they are immunised to a relevant antigen, but which does not occur in naı¨ve animals. The purpose of this study was to investigate the mechanisms of airway responsiveness to adenosine receptor agonists in anaesthetised allergic guinea pigs. 2 Inhaled adenosine 5 0 -monophosphate (AMP), the A 1 -selective adenosine receptor agonist N 6 -cyclopentyladenosine (CPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 45 publications
(76 reference statements)
5
39
1
Order By: Relevance
“…The effect of NECA is partially blocked by enprofylline, a relative selective A 2B antagonist, or MRS 1523, a selective A 3 antagonist. In allergic guinea pig model, it was reported that A 1 agonist CPA induces airway obstruction by a neuronal-dependent mechanism, whereas A 2A agonist CGS-21680 or A 3 agonist IB-MECA has no effect (Keir et al, 2006). Interestingly, it was also reported that A 3 agonist IB-MECA could contract sensitized guinea pig trachea (Martin and Broadley, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of NECA is partially blocked by enprofylline, a relative selective A 2B antagonist, or MRS 1523, a selective A 3 antagonist. In allergic guinea pig model, it was reported that A 1 agonist CPA induces airway obstruction by a neuronal-dependent mechanism, whereas A 2A agonist CGS-21680 or A 3 agonist IB-MECA has no effect (Keir et al, 2006). Interestingly, it was also reported that A 3 agonist IB-MECA could contract sensitized guinea pig trachea (Martin and Broadley, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells were claimed to be activated after adenosine challenge in allergic, but not nonallergic, patients with asthma (Bochenek et al, 2008). AMP and an A 1 receptor-selective agonist induced airway obstruction in sensitized guinea pigs by a mechanism unrelated to release of histamine from mast cells but probably through stimulation of sensory nerves and reflex activity (Keir et al, 2006). A 3 receptor signaling contributed to airway mucin secretion after allergen challenge in mice (Young et al, 2006).…”
Section: A Asthmamentioning
confidence: 99%
“…In addition, although A 1 receptors have also been shown to partially mediate adenosine-induced bronchoconstriction through a mast cell-independent pathway, targeting the A 1 receptor gene in human beings with asthma has been largely ineffective. 16,19,33,34 These observations suggest that endogenous adenosine may affect airway pathophysiology in ways other than eliciting bronchoconstriction. In this study, we have discovered that adensosine produces AHR in mice.…”
Section: The Potency Of Adenosine To Elicit Lung Mast Cell Degranulationmentioning
confidence: 99%